Curing and percolation for carbon black-epoxy-amine nanocomposites. (8th September 2019) - Wu, T.H.; Foyet, A.; Kodentsov, A.; van der Ven, L.G.J.; van Benthem, R.A.T.M.; de With, G.
Abstract: Particle agglomeration in carbon black (CB) filled epoxy (CB-E) and carbon black filled epoxy-amine (CB-EA) nanocomposites with CB concentrations ranging from 0.25 to 1.25 vol% was investigated by performing conductivity measurements as a function of time at 20 °C. For the thermoplastic CB-E samples the change in conductivity was not pronounced, while for the thermosetting CB-EA samples a percolation transition was observed appearing at ≅ 0.2 vol%. The concentration 1.25 vol% was selected for both CB-E and CB-EA samples to perform in situ isothermal electrical conductivity measurements at 20, 50, 70, and 100 °C, respectively. At higher temperature, the agglomeration process was faster, resulting in an initially sharp increase of conductivity. Despite the conductivity development of CB-EA samples being faster than that of CB-E samples, they are reaching lower final conductivity values, indicating that cluster aggregation for the CB-EA samples is restricted by polymer gelation, as confirmed by scanning and isothermal differential scanning calorimetry (DSC). Furthermore, thermodynamic DSC studies showed that no particle-particle and particle-polymer chemical reactions occurred during the epoxy-amine curing. However, physical adsorption of the epoxy and amine components on the CB particles is the likely cause for the observed slightly higher amine-epoxy reaction rates in the presence of CB. Particle agglomeration is thereby attributed to be controlled by diffusion-limited cluster aggregation (DLCA). Finally, the microstructures of CB-EA samples after curing were investigated by using TEM. The fractal dimension d f was determined and showed a smaller value as compared to the universal DLCA value, illustrating the influence of gelation on fractal formation in this system.